Estimation of combined exposure factor due to the impact of different transport related environmental pollutants air quality and noise level in Delhi city. Issue 4 (5th October 2015) - Kumar, Ravindra; Madhu, Errampalli; Maan, Anil; Sinha, Sanjeev; Akhtar, Nasim
Abstract : Purpose: – The purpose of this paper is to estimate combined exposure factor (CEF) due to impact of different transport-related environmental pollutants, air quality and noise level in Delhi city. Design/methodology/approach: – The Estimation of CEF takes into account the potential relative uptake of each pollutant (CO, NO, NO2, O3, SO2, PM10 and PM2.5 ) by the boarding and alighting of commuters at Public Transport facility and using motorcycle. With the help of CRRI mobile air pollution monitoring laboratory and previous CRRI reports. Findings: – Combined exposure to environmental pollutants is determined based on the taking weighting factor of pollutant stressor. Results shows average stressor for CO, NO, NO2, SO2, PM2.5 and noise were 2.79 mg/m3, 331.83, 210.25, 16.70, 241.3883  µ g/m3, and 72.5 dB(A), respectively. Similarly for motorcyclist, results shows average stressor for CO, NO, NO2, SO2, PM2.5 and noise were 5.1 mg/m3, 483, 398, 19.3, 295  µ g/m3, and 82.7 dB(A), respectively. The results show higher exposure value for motorcyclist. Originality/value: – Knowledge of exposure factor due to air and noise pollutant for bus commuter in sitting and standing and motorcyclist is not known for Delhi city.